Predicting poor adherence to antiretroviral therapy among treatment-naïve veterans infected with human immunodeficiency virus. Issue 2 (January 2018) - Cheng, Yan; Nickman, Nancy A.; Jamjian, Christine; Stevens, Vanessa; Zhang, Yue; Sauer, Brian; LaFleur, Joanne
Abstract : Abstract: Previous studies suggested that human immunodeficiency virus (HIV) infected patients at risk of poor adherence were not distinguishable only based on the baseline characteristics. This study is to identify patient characteristics that would be consistently associated with poor adherence across regimens and to understand the associations between initial and long-term adherence. HIV treatment-naïve patients initiated on protease inhibitors, nonnucleoside reverse transcriptase inhibitors, or integrase strand transfer inhibitors were identified from the Veteran Health Administration system. Initial adherence measured as initial coverage ratio (ICR) and long-term adherence measured as thereafter 1-year proportion days covered (PDC) of base agent and complete regimen were estimated for each patient. The patients most likely to exhibit poor adherence were African-American, with lower socioeconomic status, and healthier. The initial coverage ratio of base agent and complete regimen were highly correlated, but the correlations between ICR and thereafter 1-year PDC were low. However, including initial adherence as a predictor in predictive model would substantially increase predictive accuracy of future adherence.